Accounting Quality and Cross listing in Post-IFRSs period: Evidence from China - SHEN, Zhangheng (2010)
This study compares the China mainland cross listed firms with Hong Kong-domiciled firms and examines whether cross listed firms exhibit similar accounting quality as Hong Kong-domiciled firms. The empirical results indicate that cross listed firms have more earning smoothing, greater tendency to manage towards a target, less frequency of timely loss recognition and lower association with stock prices. It may suggest that the cross listed firms could not benefit from cross listing by committing themselves to subject to strong oversights and higher standards of external governance due to the lax enforcement of regulations and cross border jurisdiction issue. In addition, we also examine the difference of accounting quality on cross listed firms and Overseas Chinese firms, which documents significant higher accounting quality for Overseas Chinese firms than cross listed firms. These findings are consistent with previous empirical results on cross listed firms versus Hong Kong firms.